Melanin-based composite materials for multifunctional applications - Shanmuganathan, Kadhiravan; Ram, Farsa; Pimpalkar, Nikhil (256th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nanoscience, Nanotechnology and Beyond, 2018)
256th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nanoscience, Nanotechnology and Beyond